Monitoring lung impedance changes during long-term ventilator-induced lung injury ventilation using electrical impedance tomography. (5th October 2020) - Hahn, G; Niewenhuys, J; Just, A; Tonetti, T; Behnemann, T; Rapetti, F; Collino, F; Vasques, F; Maiolo, G; Romitti, F; Gattinoni, L; Quintel, M; et al.
Abstract: Objective : The target of this methodological evaluation was the feasibility of long-term monitoring of changes in lung conditions by time-difference electrical impedance tomography (tdEIT). In contrast to ventilation monitoring by tdEIT, the monitoring of end-expiratory (EELIC) or end-inspiratory (EILIC) lung impedance change always requires a reference measurement. Approach : To determine the stability of the used Pulmovista 500 ® EIT system, as a prerequisite it was initially secured on a resistive phantom for 50 h. By comparing the slopes of EELIC for the whole lung area up to 48 h from 36 pigs ventilated at six positive end-expiratory pressure (PEEP) levels from 0 to 18 cmH2 O we found a good agreement (range of r 2 = 0.93–1.0) between absolute EIT (aEIT) and tdEIT values. This justified the usage of tdEIT with its superior local resolution compared to aEIT for long-term determination of EELIC. Main results : The EELIC was between −0.07 Ωm day −1 at PEEP 4 and −1.04 Ωm day −1 at PEEP 18 cmH2 O. The complex local time pattern for EELIC was roughly quantified by the new parameter, centre of end-expiratory change (CoEEC), in equivalence to the established centre of ventilation (CoV). The ventrally located mean of the CoV was fairly constant in the range of 42%–46% of thorax diameter; however, on the contrary, the CoEEC shifted from about 40% to about 75% in the dorsal direction for PEEP levels of 14 and 18 cmH2 O. Significance : The observed shifts started earlier for higher PEEP levels. Changes of EELI could be precisely monitored over a period of 48 h by tdEIT on pigs.